PERENCANAAN KARIR SISWA SMK (Sebuah Model Berbasis Pengembangan Soft-Skill) - Sutrino, Budi (Jurnal VARIDIKA, 2013)
This study is carried out to describe the finding of students career planning model that is able to guarantee thier career improvement in work. The study was done in three SMK (vocational school) which has economics, technics, and food departement in Surakarta. Purposive sampling is selected to take SMK and based on the assumption that SMK prepares their students to enter the work. This study uses Borg and Gall model with simplification its steps. Those are (1) preliminary study, (2) model development, and (3) final model. To collect the data, he uses observation, indepth interview, quessionare, and documentation. The main instrument of this study is the researcher himself, and the assintant instruments are principals, teachers, students, parents, and department of education. The results show that the level of successness of the implementation of the finding of students career planning model is effective. It can be seen from the increase of measurement result of model application and the increase of the school in implementing soft skill and satisfaction of the user